(untitled) (ІННОВАЦІЙНА ЕКОНОМІКА, 2023)
Олексюк В.О. ОНТОЛОГІЧНІ ПЕРЕДУМОВИ ІННОВАЦІЙНОЇ МОДЕРНІЗАЦІЇ ЕКОНОМІКИ Мета. Узагальнення онтологічних передумов та особливостей інституціонального забезпечення модернізації економіки. Методика дослідження. Теоретико-методологічною основою дослідження є системний підхід до виявлення онтологічних особливостей й елементів інституціонального забезпечення модернізаційних перетворень. Теоретико-методологічною основою дослідження є системний підхід до виявлення онтологічних особливостей модернізації економіки, інституціонально-еволюційний підхід до дослідження елементів інституціонального забезпечення модернізаційних перетворень, графічний аналіз – для відображення динаміки параметрів інноваційного індексу. Результати дослідження. Акцентовано, що онтологічним фундаментом модернізаційних змін національної економіки стали специфічні реалії перехідного стану соціально-економічної системи. Констатовано, що на даному еволюційному етапі для національної економіки ключового значення набувають ефективні інститути й інновації, які в своїй сукупності становлять основу для модернізації соціально-економічної системи. Аргументовано, що модернізація забезпечує економічні й суспільні зміни та реалізує поступальний перехід соціально-економічної моделі до нового етапу розвитку. На сучасному етапі розвитку таким вектором є постіндустріальна модель, яка базується на досконалішому технологічному способі суспільного виробництва, розширенні сфери послуг, інформації і знаннях. Реалізація модернізаційного процесу потребує оптимізації регулюючих впливів та взаємодій рушійних сил трансформаційних перетворень (держави, суспільства, ринку). Наукова новизна результатів дослідження. Обґрунтовано, що регулюючі інституціональні впливи на модернізаційну динаміку в національній економіці мають враховувати глобальні трансформаційні чинники: зростання ролі інформаційно-комунікаційних технологій; поширення економічної інтеграції, експансію транснаціональних корпорацій, лібералізацію торгових відносин; орієнтацію національних господарств на зовнішні зв’язки, взаємопроникнення і взаємовплив макроекономічної політики, інтернаціоналізація освіти й культури. З огляду на завдання модернізаційних перетворень, аргументовано прийняття заходів з активізації інноваційної діяльності за допомогою обґрунтування й реалізації інструментів державної підтримки, матеріально-технічного забезпечення наукових структур сучасним інструментарієм і обладнанням для наукових досліджень, формування фінансової мотивації до продуктивної праці дослідників та впровадження європейських норм і стандартів організації й фінансування фундаментальних досліджень. Практична значущість результатів дослідження. Теоретико-методологічні положення даного дослідження поглиблюють практичний інструментарій інституціонального регулювання модернізації національної економіки. Ключові слова: модернізація, інновація, національна економіка, розвиток, трансформація, інституціональне забезпечення, інститут. Oleksiuk V.O. ONTOLOGICAL PREREQUISITES OF INNOVATIVE MODERNIZATION OF THE ECONOMY Purpose. The aim of the article is to generalize the ontological prerequisites and peculiarities of institutional support for modernization of the economy. Methodology of research. The theoretical and methodological basis of the study is a systematic approach to identifying ontological features and elements of institutional support for modernization transformations. The theoretical and methodological basis of the research is a systematic approach to identifying the ontological features of the modernization of the economy, an institutional-evolutionary approach to the study of the elements of institutional support of modernization transformations, a graphic analysis – to reflect the dynamics of the parameters of the innovation index. Findings. It is emphasized that the specific realities of the transitional state of the social and economic system became the ontological foundation of the modernization changes of the national economy. It was established that at this evolutionary stage, effective institutions and innovations, which in their totality form the basis for the modernization of the social and economic system, are of key importance for the national economy. It is argued that modernization ensures economic and social changes and realizes the progressive transition of the social and economic model to a new stage of development. At the current stage of development, such a vector is the post-industrial model, which is based on a more advanced technological method of social production, expansion of the sphere of services, information and knowledge. Implementation of the modernization process requires optimization of regulatory influences and interaction of driving forces of transformational transformations (state, society, market). Originality. It is substantiated that regulatory institutional influences on modernization dynamics in the national economy should take into account global transformational factors: the growing role of information and communication technologies; spread of economic integration, expansion of transnational corporations, liberalization of trade relations; orientation of national economies to foreign relations, interpenetration and mutual influence of macroeconomic policies, internationalization of education and culture. In view of the task of modernization transformations, the adoption of measures to activate innovative activity through the substantiation and implementation of state support tools, the material and technical support of scientific structures with modern tools and equipment for scientific research, the formation of financial motivation for the productive work of researchers and the implementation of European norms and standards are argued organization and funding of fundamental research. Practical value. The theoretical and methodological provisions of this study deepen the practical toolkit of institutional regulation of the modernization of the national economy. Key words: modernization, innovation, national economy, development, transformation, institutional support, institute.